Air Suspension-based Catching Mechanism for Mechanical Harvesting of Apples. Issue 16 (2016) - Ma, Shaochun; Karkee, Manoj; Fu, Han; Sun, Daozong; Zhang, Qin
Abstract: Bruise damage is the most critical barrier for the application of mechanical harvesting systems for fresh market apples. One of the major source of bruising is the fruit-to-catching surface and fruit-to-fruit contact when fruit detached by harvester is collected by a catching system. In this work, a fruit catching mechanism was designed and fabricated using air suspension as a cushion to minimize fruit bruising during mechanical harvesting. Various apple cultivars with different bruising susceptibility ('Granny Smith', 'Jazz', 'Honeycrisp', 'Fuji', 'Pacific Rose', and 'Pink lady') were used to evaluate the performance of an air suspension-based catching mechanism. The results showed that fruit catching with air suspension can significantly reduce the percentage of damaged apples for all of six cultivars evaluated in this work compared to fruit catching without air suspension. It was found that the decrease in fruit damage rate with air suspension ranged from 14.5 to 36.9% for different cultivars. The effect of air suspension on the percentage of downgraded apples was not significant (compared to catching apples without air suspension) except for Pink Lady cultivar. The reduction in downgraded fruit ranged from 3% to 9.3% among different cultivars (except for Pink Lady(19%)).